The Variable Impact of the Global Economic Crisis in South East Europe - Bartlett, Will; Prica, Ivana (Economic Annals, 2011)
This paper studies the variable impact of the global economic crisis on the countries of South East Europe. The central question is whether the institutional reforms introduced during the transition period have enabled countries to cope with external shocks such as those associated with the recent global economic crisis. The transmission mechanisms of the crisis to the region are identified as contractions of credit, foreign direct investment, remittances, and exports, and their variable impact across countries is assessed. Several types of institutions are examined, including the degree to which countries have adopted the acquis communautaire, determined by the extent of their EU integration, progress with transition, and the broad institutional environment measured through the quality of governance. The paper asks whether countries with a more flexible economy due to faster progress with transition reforms were better able to adjust to the impact of external shocks. It concludes that the variable impact of the global crisis in the region can be explained mainly by their degree of integration into the global economy, and that the institutional reforms that were introduced during the boom times have made countries more integrated into the global economy, and therefore more vulnerable to the impact of the global economic crisis.